How do we cultivate in England? Tillage practices in crop production systems - Townsend, Toby J.; Ramsden, Stephen J.; Wilson, Paul (Wiley, 2016)
Reducing tillage intensity offers the possibility of moving towards sustainable intensification objectives. Reduced tillage (RT) practices, where the plough is not used, can provide a number of environmental and financial benefits, particularly for soil erosion control. Based on 2010 harvest year data from the nationally stratified Farm Business Survey and drawing on a sub-sample of 249 English arable farmers, we estimate that approximately 32% of arable land was established under RT, with 46% of farms using some form of RT. Farms more likely to use some form of RT were larger, located in the East Midlands and South East of England and classified as ‘Cereals’ farms. Application of RT techniques was not determined by the age or education level of the farmer. Individual crops impacted the choice of land preparation, with wheat and oilseed rape being more frequently planted after RT than field beans and root crops, which were almost always planted after ploughing. This result suggests there can be limitations to the applicability of RT. Average tillage depth was only slightly shallower for RT practices than ploughing, suggesting that the predominant RT practices are quite demanding in their energy use. Policy makers seeking to increase sustainable RT uptake will need to address farm-level capital investment constraints and target policies on farms growing crops, such as wheat and oilseed rape, that are better suited to RT practices.